Integrasi Pendekatan MBC dan SBSC dalam Menyusun Strategi Pengelolaan Ekowisata Tangkahan, Taman Nasional Gunung Leuser, Sumatera Utara, Indonesia - Yooce Yustiana; Intan Khoirunnisa; Nandang Prihadi (Faculty of Forestry Universitas Gadjah Mada, 2023)
Indonesia as mega-biodiversity country and various unique local wisdom activities are main attractions that can be enjoyed by world tourists. Global tourism trends to go back to nature drive development of ecotourism. Tangkahan is ecotourism area that offers variety of tourist attractions. However, as time goes by, Tangkahan ecotourism also faced some challenges that effect efficiency and effectiveness of organization. Therefore, it is necessary to design ecotourism performance strategy, that can be used to integrate business model canvas (BMC) into sustainable balanced scorecard (SBSC). This study aims to describe performance of business model using BMC, analyze performance business model using SWOT, and design performance management strategy by integrating BMC into SBSC. Field data in the form of primary and secondary data. Data analysis used to describe business model is BSC and SWOT, and strategy design used SBSC and PLS-SEM. Results of this study have confirmed that Tangkahan Ecotourism can be described by BMC with value proposition, key resources, key activities, key partnerships, customer segment, channels, customer relationship, revenue streams and cost structures. Evaluation results, suggest new BMC description, that needs to enhance and increase existing aspects of elements BMC owned. There are 16 strategies obtained from SBSC management strategy design.